Changes in Chemical Properties of Sipramin-Affected Paddy Soil during Incubation with Humic Acid and Nitrogen Fertilizer - Melinda Trisya Yulianto; Wanti Mindari; Rossyda Priyadarshini (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2026)
Continuous use of Sipramin fertilizer can lead to sodium (Na+) accumulation in the soil. Sodium accumulation damages soil physical properties, which also affects the chemical quality and nutrient supply. This study aimed to evaluate the effects of various doses of humic acid and nitrogen fertilizer sources on soil chemical properties. This study was arranged in a factorial completely randomized design (CRD) with 2 factors: humic acid doses (0, 20, 40, and 60 kg ha-1) and nitrogen fertilizer types (control, NPK Phonska, Urea, KNO₃, and MAP) with a recommended rate of 92 kg ha-1. The study consisted of 20 treatment combinations with 3 replications, yielding a total of 60 experimental units arranged randomly. Soil samples were collected at 7 and 21 days after treatment (DAT) to analyze pH, organic C, cation exchange capacity (CEC), exchangeable Na, and available N (NH₄⁺ and NO₃-). The results showed that the interaction between humic acid and nitrogen fertilizer did not significantly affect the chemical properties of the Sipramin-affected soil. In general, the effects of both treatments depended on the parameters and the time of observation. At 7 DAT, several variables showed significant effects, whereas at 21 DAT, some of those effects were no longer significant.